The Role of Organizational Citizenship Behaviour (OCB) , Intrinsic Motivation and Job Satisfaction on Employee Performance of Online Shop - Moh. Sutoro; Hamsinah Hamsinah; Denok Sunarsi (Jurnal Manajemen Industri dan Logistik, 2023)
The purpose of this study was to analyze the relationship of OCB to employee performance, intrinsic motivation to employee performance and job satisfaction to employee performance.Online questionnaire given to respondents who are online shop employees. Through the Whatsapp network, questionnaires were distributed. While literature, books, and websites used as a secondary data source. The population used consisted of 2013 permanent employees from all online shops . This research uses probability sampling method by using simple random sampling as the sampling method. Due to the large number of respondents, the number of samples in this study was calculated using the Slovin equation and the number of respondents who became the sample was 103 people. In this study, the analysis uses structural equation modeling (SEM) with data processing tools using smartPLS 3.0 software. The results of this study are OCB has a positive impact on employee performance, intrinsic motivation has a positive impact on employee performance and job satisfaction has a positive effect on employee performance.